Technology Adoption Barriers and System Usability in Blended Learning Environments: A Case Study-Based Quality Framework Development - Masthurah, Nur; Dollah, Syarifuddin; Abduh, Amirullah; Amin, Fatimah Hidayahni; Markuna (Journal of Applied Science, Engineering, Technology, and Education, 2026)
This study investigated the challenges experienced by students in an English for Public Speaking course during the implementation of blended learning instruction. This study employed a qualitative descriptive design to examine students’ challenges in the implementation of blended learning instruction in an English for Public Speaking course. Data were collected from three classes in the Business English Communication Study Program at Universitas Negeri Makassar through document analysis, classroom observations, and semi-structured interviews. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which consists of data condensation, data display, and conclusion drawing/verification, to identify and verify the recurring challenges experienced by students in blended public speaking instruction. The findings revealed four major categories of challenges. First, students encountered linguistic and content-related difficulties, including limited vocabulary, grammatical inaccuracies, and problems in organizing coherent and persuasive arguments. Second, methodological challenges emerged from unclear instructional guidelines, limited lecturer–student interaction, and insufficiently engaging asynchronous learning activities. Third, practical challenges were associated with unstable internet connectivity, limited access to reliable digital devices, and inadequate digital literacy. Fourth, psychological challenges, particularly speaking anxiety, fear of making mistakes, and low self-confidence, negatively affected students’ public speaking performance. These challenges were interconnected and collectively shaped students’ learning experiences in the course of English for Public Speaking. This study offered a holistic understanding of students’ challenges in the implementation of blended learning instruction in an English for Public Speaking course. By highlighting the interrelationship among linguistic, methodological, practical, and psychological factors, the study contributed to the development of more responsive blended learning practices that supported students’ communicative competence and public speaking development.